Key technologies and challenges of 6G - Lu Xujun; Zheng Jianfei; Xia Zhu (Dianzi Jishu Yingyong)
6G and future communication system networks will meet the requirements of a world fully connected, and revolutionary technology solutions are expected to drive the rapid growth of smart devices and service applications. This paper conducts in-depth research on topics related to significant technological applications to achieve 6G connectivity goals, including terahertz communication with broader network operations, intelligent communication environment, artificial intelligence, network automation, ambient backscatter communication, Internet of Space Things with cubesats and UAVs, cellular-free massive MIMO communication, and more. The possible problems and challenges arising from the application of the technology are also discussed.